2019
DOI: 10.12659/msm.917068
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Genes Involved in Atherosclerotic Macrophages: Insights from Microarray Data Mining

Abstract: Background: In an atherosclerotic artery wall, monocyte-derived macrophages are the principal mediators that respond to pathogens and inflammation. The present study aimed to investigate potential genetic changes in gene expression between normal tissue-resident macrophages and atherosclerotic macrophages in the human body. Material/Methods: The expression profile data of GSE7074 acquired from the Gene Expression Omnibus (GEO) database, which includes the transcriptome of 4 types of macrophages, was downloaded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…This gene is also known as PSMD6-AS2, a gene that could disrupt expression of a proteasome subunit. This gene was identified as differentially expressed in a study of atherosclerotic macrophages [ 40 ]. Another proteasomal subunit, PSMC3 mutation is associated with subcutaneous calcifications [ 41 ], indicating that this lincRNA RP11-245 J9.5 might be involved in atherosclerosis by regulating several proteasome subunits.…”
Section: Discussionmentioning
confidence: 99%
“…This gene is also known as PSMD6-AS2, a gene that could disrupt expression of a proteasome subunit. This gene was identified as differentially expressed in a study of atherosclerotic macrophages [ 40 ]. Another proteasomal subunit, PSMC3 mutation is associated with subcutaneous calcifications [ 41 ], indicating that this lincRNA RP11-245 J9.5 might be involved in atherosclerosis by regulating several proteasome subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al discovered three differentially expressed genes ( KDELR3 , CD55 , and DYNC2H1 ) can serve as diagnostic and therapeutic targets in AS macrophages through microarray analysis ( Huang et al, 2019 ). Wang et al (2019) constructed a miRNA-TF-gene network through microarray data analysis in the AS macrophages. However, these studies only concentrated on the characterization of potential biomarkers, and the samples size of the dataset is small, which leads to low accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are highly conserved ncRNAs that exert versatile biological functions. [36][37][38] Wu et al indicated that PVT1 silencing could prevent the development of uveal melanoma through impairing miR-17-3p-dependent MDM2 upregulation. 39 Furthermore, PVT1 could modulate the proliferation and apoptosis of lens epithelial cells in diabetic cataract through regulation miR-214-3p/MMP2 axis.…”
Section: Discussionmentioning
confidence: 99%